Modeling of hydrogen production with a stand-alone renewable hybrid power system - DURSUN, ERKAN; KILIÇ, OSMAN (PERGAMON-ELSEVIER SCIENCE LTD, 2012)
Hydrocarbon resources adequately meet today's energy demands. Due to the environmental impacts, renewable energy sources are high in the agenda. As an energy carrier, hydrogen is considered one of the most promising fuels for its high energy density as compared to hydrocarbon fuels. Therefore, hydrogen has a significant and future use as a sustainable energy system. Conventional methods of hydrogen extraction require heat or electrical energy. The main source of hydrogen is water, but hydrogen extraction from water requires electrical energy. Electricity produced from renewable energy sources has a potential for hydrogen production systems. In this study, an electrolyzer using the electrical energy from the renewable energy system is used to describe a model, which is based on fundamental thermodynamics and empirical electrochemical relationships. In this study, hydrogen production capacity of a stand-alone renewable hybrid power system is evaluated. Results of the proposed model are calculated and compared with experimental data. The MATLAB/Simscape (R) model is applied to a stand-alone photovoltaic-wind power system sited in Istanbul, Turkey. Copyright (C) 2011, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Renewable hydrogen production; Electrolyzer; Modeling; ENERGY MANAGEMENT; SIMULATION